2011
DOI: 10.1534/genetics.111.131482
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy Is Associated with Ribosomal Protein Gene Haplo-Insufficiency inDrosophila melanogaster

Abstract: The Minute syndrome in Drosophila melanogaster is characterized by delayed development, poor fertility, and short slender bristles. Many Minute loci correspond to disruptions of genes for cytoplasmic ribosomal proteins, and therefore the phenotype has been attributed to alterations in translational processes. Although protein translation is crucial for all cells in an organism, it is unclear why Minute mutations cause effects in specific tissues. To determine whether the heart is sensitive to haplo-insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Several RPs have been implicated in the development and progression of cardiovascular diseases . For instance, the Minute syndrome in Drosophila , which is associated with RP haploinsufficiency, also affects the heart . The cardiomyopathy associated with the Minute syndrome is caused by haploinsufficiency for genes encoding cytoplasmic RPs.…”
Section: Ribosomal Proteins and The Pathogenesis Of Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several RPs have been implicated in the development and progression of cardiovascular diseases . For instance, the Minute syndrome in Drosophila , which is associated with RP haploinsufficiency, also affects the heart . The cardiomyopathy associated with the Minute syndrome is caused by haploinsufficiency for genes encoding cytoplasmic RPs.…”
Section: Ribosomal Proteins and The Pathogenesis Of Human Diseasesmentioning
confidence: 99%
“…The cardiomyopathy associated with the Minute syndrome is caused by haploinsufficiency for genes encoding cytoplasmic RPs. Specifically, the heart‐specific knockdown of S15a severely impairs the cardiac function in adult Drosophila . RPs also have a role in the vascular system.…”
Section: Ribosomal Proteins and The Pathogenesis Of Human Diseasesmentioning
confidence: 99%
“…The Drosophila heart is sensitive to alterations in structural and contractile proteins that can alter contractility (Wolf et al 2006; Allikian et al 2007; Taghli-Lamallem et al 2008), as well as signaling in pathways such as Notch, Rhomboid 3, SMAD, and insulin and ribosomal functions can change heart function in flies (Goldstein et al 2011; Yu et al 2010; Kim et al 2010; Wessells et al 2004; Casad et al 2011). Large scale RNAi screening and proteomics studies have also identified complexes important for Drosophila heart function (Neely et al 2010; Cammarato et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several r-proteins were identified as causative factors of various CVDs, including r-protein Rps15, implicated in the progression of cardiomyopathy [145], and Rpl17, malfunctions of which have been linked to the development of carotid atherosclerotic vascular disease [146]. What makes these r-proteins pro-pathogenic remains unanswered.…”
Section: Ribosomementioning
confidence: 99%